ANALISIS EFEKTIFITAS DAN KELAYAKAN JEMBATAN PENYEBERANGAN ORANG (JPO) PASAR TRADISIONAL - MODERN KOTA PRABUMULIH - Muizzi, Lukman Muizzi; Sarwandy, M. Hijrah Agung; Agustini, Marice Agustini (Universitas Muhammadiyah Palembang, 2023)
To improve the safety, security and comfort of pedestrians when crossing the street, the government ofPrabumulih City has built a Pedestrian Crossing Bridge located at the Traditional- Modern Market inPrabumulih City. Pedestrian crossing bridges are pedestrian bridges that are located across the road orrailroad tracks and are only intended for pedestrians who want to cross the highway or railroad tracks.The pedestrian crossing bridge is a crossing facility that is needed by the community to pass through trafficlanes and is very necessary in order to reduce the possibility of accidents and for the safety of pedestrianswho pass through it. The results of the survey on the volume of pedestrians crossing, the highest volume ofpedestrians using pedestrian crossing bridges was 186 people and 586 people not using pedestrian crossingbridges. Based on the results of the calculation of the effectiveness of the pedestrian crossing bridge, it wasfound that it was 26.14%, so the effectiveness of the pedestrian crossing bridge was included in theineffective category. For the feasibility of the Pedestrian Crossing Bridge based on the component of thefeasibility standard, it has met the eligibility standard. Meanwhile, the characteristics of pedestriancrossings that were most responded to by respondents who used pedestrian crossing bridges were that theyfelt the glass design on the bridge disturbed the view when crossing the bridge with a percentage of 76%,while for respondents who crossed not using pedestrian crossing bridges but through the road medianbecause faster than using a pedestrian bridge by 76.8%.